Some concepts of social psychology in India - Sharma, Sagar (1980)
Studies in Hindu social psychology up to the early 1970's were reviewed. It was concluded that cross-cultural research still has not found strong grounding in the Indian psychological community. It was noted that very few researches actually focused on indigenous concepts and that very rarely were such concepts studies using culturally sensitive instruments. To facilitate the movement of India's research work towards ethic analysis, central concepts were abstracted from the Hindu religion which were believed to to also be key concepts in the social psychology of the Hindus. The concept of class/caste, the doctrine of transmigration of samsara, and the tendency towards inclusiveness were among the concepts cited as central to the understanding of Hindu psychology. Included also in this study were some reflections on the consequences of such religious values on the life of an individual and on society. Finally, some chartered paths towards a healthy modernization of the Hindu were presented.
Includes bibliographical references (pages 58-64).